2012
DOI: 10.1111/jnc.12035
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐ and stress‐activated kinases regulate progenitor cell proliferation and neuron development in the adult dentate gyrus

Abstract: The neurogenic niche within the subgranular zone (SGZ) of the dentate gyrus is a source of new neurons throughout life. Interestingly, SGZ proliferative capacity is regulated by both physiological and pathophysiological conditions. One outstanding question involves the molecular mechanisms that regulate both basal and inducible adult neurogenesis. Here, we examined the role of the MAPK-regulated kinases MSK1 and MSK2 (mitogen and stress activated kinase 1 and 2) as regulators of dentate gyrus SGZ progenitor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 62 publications
(109 reference statements)
3
25
0
Order By: Relevance
“…Further, fluorescent immunolabeling for pMSK1 and the progenitor cell marker Sox-2, indicated that the activated form of the kinase is expressed in progenitor cell populations of the SGZ at 2 DPI (Figure 1E). These data, coupled with prior work from our lab (Choi et al, 2012) showing MSK1 expression in SGZ progenitor cells, strongly suggest that ischemia triggers MSK1 activation in progenitor cells…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Further, fluorescent immunolabeling for pMSK1 and the progenitor cell marker Sox-2, indicated that the activated form of the kinase is expressed in progenitor cell populations of the SGZ at 2 DPI (Figure 1E). These data, coupled with prior work from our lab (Choi et al, 2012) showing MSK1 expression in SGZ progenitor cells, strongly suggest that ischemia triggers MSK1 activation in progenitor cells…”
Section: Resultssupporting
confidence: 75%
“…Using the same set of DCX/BrdU labeled tissues, co-labeled cells were qualitatively categorized into stages of neuronal development based on morphology (Figure 5). Stages were defined as previously reported (Choi et al, 2012). Briefly, stage 1 cells were defined as having no processes; stage 2 cells were defined as having short processes extending into the GCL; stage 3 cells were defined as those extending long processes into the molecular layer; and stage 4 cells were defined as having long processes and branches extending into the molecular layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, MAPK signaling is rapidly activated by cerebral ischemia (Gu et al, 2001; Wu et al, 2000) and regulates both cytoplasmic and nuclear targets to promote cell growth, differentiation and apoptosis (Pan et al, 2012; Zhang and Liu, 2002). Regulation of these processes occurs via both direct ERK phosphorylation of transcription factors (Zhang and Liu, 2002) and also via phosphorylation of downstream effector kinases such as the mitogen and stress-activated kinase (MSKs) and ribosomal S6 kinases (RSKs) (Choi et al, 2012; Hauge and Frödin, 2006; Karelina et al, 2012; Yves et al, 2012), which are the focus of the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, blood-brain barrier (BBB) leakage has been reported following pilocarpine-induced SE, which may provide an environment for peripheral leukocyte infiltration. On the other hand, when examined 2 days after SE, pilocarpine-induced SE increased progenitor cell proliferation in the subgranular zone through insulin-like growth factor-1 (IGF-1)-ERK-MSK signaling pathways [4,5]. Considering the distinct roles of Tbr2 in proliferation and differentiation of progenitor cells as well as in the infiltration of CD8+ T cells and natural killer cells, it may be interesting to investigate the intervention of Tbr2 in progenitor cell proliferation and/or immune reaction following SE.…”
Section: Introductionmentioning
confidence: 99%